GASTRIC CANCER IN TOMSK REGION: EPIDEMIOLOGICAL ASPECTS - L. F. Pisareva; I. N. Odintsova; O. A. Ananina; S. G. Afanasyev; M. Yu. Volkov; I, N, Davydov (Сибирский онкологический журнал)
Gastric cancer remains the most common cancer both worldwide and in the Russian Federation. Gastric cancer is the 3-rd most common cancer in men, comprising 9,1 % of all cancer cases and the 4-th most common cancer in women comprising 5,8 % of all cancer cases in Tomsk region in 2011. From 2000 to 2011, the crude and age-standardized gastric cancer incidence rates decreased by 13,4 % and 25,7 %, respectively in males and increased by 22,6 % and 11,1 %, respectively in females. In addition, the increase in gastric cancer incidence rate was observed in both male and female elderly population of Tomsk region.